''Coronary Blindness: Desensitization after excessive exposure to coronavirus-related information''. Issue 3 (September 2022) - MS, Kadir Uludag
Highlights: Coronavirus epidemic has drastically impacted the publishing system of the journals. Many journals have swiftly approved articles to avoid delay in publication. Many articles written regarding the Coronavirus situation may lead people to be less interested in the topic.